Power output, thermal efficiency and exergy-based ecological performance optimizations of an irreversible KCS-34 coupled to variable temperature heat reservoirs. (1st February 2020) - Feng, Huijun; Qin, Wanxu; Chen, Lingen; Cai, Cunguang; Ge, Yanlin; Xia, Shaojun
Highlights: A variable temperature heat reservoir irreversible KCS-34 model is established. Finite-time thermodynamics is applied for performance optimization. Power, efficiency and ecological function are derived and maximized. Heat transfer area distributions are optimized for three objectives. Three objectives are increased by 17.27%, 5.79% and 1.05%, respectively. Abstract: An irreversible Kalina cycle system 34 (KCS-34) model with variable temperature heat reservoirs is studied by using finite-time thermodynamics. The power output, thermal efficiency and exergy-based ecological function of the KCS-34 are derived, and the effects of evaporator outlet dryness and mass flow rate of the working fluid on these performances are analyzed. With constant total heat transfer area, the heat transfer area distributions are optimized, and the optimal performances of the KCS-34 are obtained. The results show that the power output, thermal efficiency and ecological function have their triple maximum by optimizing the heat transfer area distributions, and the optimal distributions are different from each other. The ecological function shows a trade-off between power output and thermal efficiency to some extent. Compared with the initial designs, the power output, thermal efficiency and ecological function after triple optimizations of the heat transfer area distributions are increased by 17.27%, 5.79% and 1.05%, respectively. It shows that parameter optimization is important to improve the performances of the KCS-34, and the corresponding optimization work is significant.